A Novel Perspective Linkage Between Kidney Function and Alzheimer’s Disease - Shi, Yan; Liu, Zhangsuo; Shen, Yong; Zhu, Hanyu (Frontiers in Cellular Neuroscience, 2018)
It has long been believed that kidney function is linked to brain activity. Clinical studies demonstrate that patients with chronic kidney disease (CKD) are more prone to cognitive impairment and Alzheimer’s disease (AD), and the degree of cognitive impairment is closely related to CKD progression and renal failure. Moreover, the fact that cognitive function in CKD patients is significantly improved after successful kidney transplantation reveals a linkage between CKD and AD. However, the mechanisms behind this linkage are unclear. The physiological function of the kidney is to maintain the stability of the internal environment, including the cerebrovascular circulation, whereas abnormal kidney function often leads to ischemia and hypoxia. Many CKD patients experience chronic hypoxia, and many urinary toxins accumulate after renal function is impaired. In this mini review, we will propose a novel perspective on the association between AD and CKD and the connection between the kidney and brain.